Fibroblast growth factor 8 regulates postnatal development of paraventricular nucleus neuroendocrine cells. Issue 1 (December 2015) - Rodriguez, Karla; Stevenson, Erica; Stewart, Courtney; Linscott, Megan; Chung, Wilson
Abstract Background Fibroblast growth factors (FGFs) are crucial signaling molecules that direct the development of the vertebrate brain. FGF8 gene signaling in particular, may be important for the development of the hypothalamus–pituitary–adrenal (HPA)-axis. Indeed, newbornFgf8 hypomorphic mice harbor a major reduction in the number of vasopressin (VP) neurons in the paraventricular nucleus (PVN), the central output component of the HPA-axis. Additionally, recent studies indicated that adult heterozygous (+/neo )Fgf8 hypomorphic mice exhibit more anxiety-like behaviors than wildtype (WT) mice. These studies led us to investigate whetherFgf8 hypomorphy abrogated VP and/or corticotropin-releasing hormone (CRH) neuronal development in the postnatal day (PN) 21 and adult mouse PVN. Furthermore, we studied whetherFgf8 hypomorphy disrupted HPA responsiveness in these mice. Methods Using immunohistochemistry, we examined the development of VP and CRH neurons located in the PVN of PN 21 and adultFgf8 +/neo mice. Moreover, we used a restraint stress (RS) paradigm and measured corticosterone levels with enzyme immunoassays in order to assess HPA axis activation. Results The number of VP neurons in the PVN did not differ between WT andFgf8 +/neo mice on PN 21 and in adulthood. In contrast, CRH immunoreactivity was much higher inFgf8 +/neo mice than in WT mice on PN 21, this difference was no longer shown in adult mice. RS caused a higher increase in corticosterone levels in adultFgf8 +/neo mice than in WT mice after 15 min, but no difference was seen after 45 min. Conclusions First, Fgf8 hypomorphy did not eliminate VP and CRH neurons in the mouse PVN, but rather disrupted the postnatal timing of neuropeptide expression onset in PVN neurons. Second, Fgf8 hypomorphy may, in part, be an explanation for affective disorders involving hyperactivity of the HPA axis, such as anxiety.